Stabilization of a Class of Stochastic Systems with Time Delays - Jian Wang; Cuixia Li (Journal of Applied Mathematics)
The problem of exponential stability is investigated for a class of stochastic time-delay systems. By using the decomposition technique and Lyapunov stability theory, two improved exponential stability criteria are derived. Finally, a numerical example is given to illustrate the effectiveness and the benefit of the proposed method.